Association of HDL cholesterol efflux capacity with incident coronary heart disease events: a prospective case-control study. Issue 7 (July 2015) - Saleheen, Danish; Scott, Robert; Javad, Sundas; Zhao, Wei; Rodrigues, Amrith; Picataggi, Antonino; Lukmanova, Daniya; Mucksavage, Megan L; Luben, Robert; Billheimer, Jeffery; Kastelein, John J P; Boekholdt, S Matthijs; et al.
Summary Background Although HDL cholesterol concentrations are strongly and inversely associated with risk of coronary heart disease, interventions that raise HDL cholesterol do not reduce risk of coronary heart disease. HDL cholesterol efflux capacity—a prototypical measure of HDL function—has been associated with coronary heart disease after adjusting for HDL cholesterol, but its effect on incident coronary heart disease risk is uncertain. Methods We measured cholesterol efflux capacity and assessed its relation with vascular risk factors and incident coronary heart disease events in a nested case-control sample from the prospective EPIC-Norfolk study of 25 639 individuals aged 40–79 years, assessed in 1993–97 and followed up to 2009. We quantified cholesterol efflux capacity in 1745 patients with incident coronary heart disease and 1749 control participants free of any cardiovascular disorders by use of a validated ex-vivo radiotracer assay that involved incubation of cholesterol-labelled J774 macrophages with apoB-depleted serum from study participants. Findings Cholesterol efflux capacity was positively correlated with HDL cholesterol concentration (r=0·40; p<0·0001) and apoA-I concentration (r=0·22; p<0·0001). It was also inversely correlated with type 2 diabetes (r=–0·18; p<0·0001) and positively correlated with alcohol consumption (r=0·12; p<0·0001). In analyses comparing the top and bottom tertiles, cholesterol efflux capacity was significantly and inversely associated with incident coronary heart disease events, independent of age, sex, diabetes, hypertension, smoking and alcohol use, waist:hip ratio, BMI, LDL cholesterol concentration, log-triglycerides, and HDL cholesterol or apoA-I concentrations (odds ratio 0·64, 95% CI 0·51–0·80). After a similar multivariable adjustment the risk of incident coronary heart disease was 0·80 (95% CI 0·70–0·90) for a per-SD change in cholesterol efflux capacity. Interpretation HDL cholesterol efflux capacity might provide an alternative mechanism for therapeutic modulation of the HDL pathway beyond HDL cholesterol concentration to help reduce risk of coronary heart disease. Funding US National Institutes of Health, UK Medical Research Council, Cancer Research UK.